Natural Philosophy in Children's Songs on YouTube “Marah KG”: A Study of Onomatopoeia and Its Meaning - Putri, Firsya Aulia; Wargadinata, Wildana; Munjiah, Ma’rifatul (Raja Zulkarnain Education Foundation, 2025)
The purpose of this study is to reveal Arabic words formed from the imitation of natural sounds (onomatopoeia) in a collection of children's songs on Youtube “Marah KG”. This research uses descriptive qualitative method with semantic approach of Bredin's onomatopoeia theory (1996). There are two kinds of data sources used, namely primary and secondary. Primary data are song lyrics in the collection of children's songs on Youtube “Marah KG”, especially the playlist Jami' Aghaniy Qonat Marah KG-Maktabah Al-Aghaniy Al-Kamilah. The secondary data comes from books, journal articles, and other literatures relevant to the study of onomatopoeia. Data collection techniques used four techniques, namely listening, reading, note-taking, and documentation techniques. The data analysis technique used is Miles & Huberman's, namely data reduction, data presentation, and conclusion drawing. Based on the results of this study, there are 7 Arabic words formed from the imitation of natural sounds (onomatopoeia) consisting of two types of onomatopoeia, namely direct onomatopoeia and associative onomatopoeia. Meanwhile, the meanings contained consist of 3 meanings, namely referential meaning, contextual meaning, and associative meaning.